2017
DOI: 10.1080/09687599.2017.1382322
|View full text |Cite
|
Sign up to set email alerts
|

Theorising everyday life after acquired brain injury

Abstract: This paper provides a conceptual argument for the sociological analysis of the everyday experiences of disabled people through the example of acquired brain injury (ABI) survivors. Most research concerning ABI has been carried out within a medical framework. This paper adds a new dimension to research concerning ABI, and indeed, to my knowledge, is the first to explore a long-term, interdisciplinary view of both ABI and neurological rehabilitation. This paper sets out how the use of critical sociological theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…We found that these engagements were characterised by loss, disruption, gain and flow at the same time. This entails a shift in focus away from what is lost, towards potential and what the future may hold (Harvey, 2018). This vision of 'becoming' can be specified in a network of places that ABI survivors wish to explore, where they want to interact in a fluid, dynamic and balanced way, by taking into account their (dis) abilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that these engagements were characterised by loss, disruption, gain and flow at the same time. This entails a shift in focus away from what is lost, towards potential and what the future may hold (Harvey, 2018). This vision of 'becoming' can be specified in a network of places that ABI survivors wish to explore, where they want to interact in a fluid, dynamic and balanced way, by taking into account their (dis) abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has shown that ABI survivors and their families are dealing with independence and community participation, by balancing and coordinating different ways of being independent and participative at places where they wish to (inter)act. So, in everyday life, independence and participation are neither single, coherent, factors nor clear-cut, stable goals (Harvey, 2018;Struhkamp et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It is a feature of normal human life, 25 even where people assume they are fully independent. 20 In short, when people are unable to achieve independence in all domains in rehabilitation, this does not mean that they are fundamentally different from others. In recognition of this reality, the field of intellectual disability now includes the idea of positive interdependencies in their goals.…”
Section: Are Healthy People Actually Independent?mentioning
confidence: 99%
“…One important social domain is employment. 20,32 A key issue in employment is discrimination and stigma, 1,35 where people view a person in terms of their disability and no longer see them as an individual but as a stereotype. Stigma leads people automatically to infer from a visible disability that the injured person is less competent in other domains, even when they are highly skilled.…”
Section: Achieving Social Engagementmentioning
confidence: 99%
See 1 more Smart Citation